Pemahaman Praktis Strategi Influencer Promosi Pariwisata - Alma Mandjusri; Edoardo Irfan (Journal of Tourism and Creativity, 2019)
Abstract This article is a part of “Tourism, Creativity, Communication, and Transformation” book written by Poerwanto. It discusses the ICT in tourism promotion. In this ICT era, tourism promotional activities have been applied in a various way, and one of them is using influencer. Influencer is a person or a party that directs others in buying decision process. Many celebrities become influencers that endorse a tourism brand or destination on their social media and they have proven able to influence their followers to buy the promoted brand. A strategy using influencer must be selected to inform in a right way and the base of that strategy is the offered service quality of the tourism object. Keyword: influencer strategy, tourism promotion